2016
DOI: 10.1021/acs.inorgchem.6b02336
|View full text |Cite
|
Sign up to set email alerts
|

Cp*-Substituted Boron Cations: The Effect of NHC, NHO, and CAAC Ligands

Abstract: The effect of a ligand on the electron deficiency and Lewis acidity of the Cp*-substituted boron dication has been investigated experimentally and theoretically. In addition to the reported IMes- and N-heterocyclic olefin (NHO)-stabilized boron dications, the related cyclic alkylamino carbene (CAAC)-coordinated boron mono- and dications have also been synthesized and structurally characterized. An electrochemical study of dications [3a-3c] confirms the higher electron deficiency of the dicationic system than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 41 publications
0
12
0
1
Order By: Relevance
“…7 Similarly, Chiu and co-workers showed that a cAAC adduct of the [Cp*B] 2+ dication underwent hydride addition at the ylidene carbon upon reaction with [ n Bu 4 N] + [BH 4 ] – . 15 To our knowledge, however, a 1,2-hydrogen shift from boron to a carbene unit has never been reported.…”
Section: Resultsmentioning
confidence: 83%
“…7 Similarly, Chiu and co-workers showed that a cAAC adduct of the [Cp*B] 2+ dication underwent hydride addition at the ylidene carbon upon reaction with [ n Bu 4 N] + [BH 4 ] – . 15 To our knowledge, however, a 1,2-hydrogen shift from boron to a carbene unit has never been reported.…”
Section: Resultsmentioning
confidence: 83%
“…Therole of CAACsinGroup 13 element chemistry is not limited to the preparation of nucleophilic organoborons.They have been used for the stabilization of neutral boron and aluminum radicals 13 and 14, [80] and radical cation 15 [66] (Scheme 8). Interestingly,C hiu et al [81] were not only able to isolate the CAAC-stabilized boron cation 16 and dication 18,b ut also the NHC analogues.H owever,w hile the reduction of the CAAC complexes 16 and 18 gave rise to the corresponding neutral radical 17 and radical cation 19, respectively,n op aramagnetic species could be characterized with the NHC complexes.T his is one of the numerous illustrations of the superiority of CAACs over NHCs for the stabilization of radicals.…”
Section: Caacs In Group 13 Element Chemistrymentioning
confidence: 98%
“…They have been used for the stabilization of neutral boron and aluminum radicals 13 and 14 , and radical cation 15 (Scheme ). Interestingly, Chiu et al . were not only able to isolate the CAAC‐stabilized boron cation 16 and dication 18 , but also the NHC analogues.…”
Section: Caacs In Group 13 Element Chemistrymentioning
confidence: 99%
“…Auch die neutralen Bor‐ und Aluminiumradikale 13 und 14 sowie das Radikalkation 15 konnten mithilfe von CAACs stabilisiert werden (Schema ). Chiu und Mitarbeiter konnten, außer dem CAAC‐stabilisierten Borkation 16 und Bordikation 18 , auch die entsprechenden NHC‐Analoga isolieren. Dass die CAACs bezüglich der Stabilisierung von Radikalen den NHCs überlegen sind, zeigt sich daran, dass die Reduktion der CAAC‐Verbindungen 16 und 18 zum neutralen Radikal 17 bzw.…”
Section: Caacs In Der Chemie Der Gruppe‐13‐elementeunclassified